El concepto de documento desde una perspectiva interdisciplinar: de la diplomática a la archivística - García Ruipérez, Mariano; Galende Díaz, Juan Carlos (Revista General de Información y Documentación, 2003)
Whereas the object of Diplomatic is documents, that of Archival Sciences is archives in the sense of organized sets of documents. The concept of document has changed in the course of time and has been used with different meanings by very different disciplines. The article analyses this concept from the point of view of Diplomatic, Documentation Sciences, History, Administrative Law, and Archival Science, distinguishing its principles and elements and seeking similarities and differences.